The Effect of Flipped Classroom Learning in Enhancing Mathematics Learning Outcomes of Blind Students During The Pandemic - Oryza Lisativani Fatimah; Rara Adiningsih; Fitriyana Desynta Lubis; Abdul Halim Fathani (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
This study aims to analyze the effect of Flipped Classroom learning on the mathematics learning outcomes of blind students during the Covid-19 pandemic. This type of research is Quasi-Experimentals with Nonequivalent Control Group Designs. The population used in this research is the blind students of class V and class VI of SLBN ABD Kedungkandang Malang city with 12 students. Samples were taken using a saturated sampling technique. The experimental class uses the Flipped Classroom learning model for class VI students, and the control class uses a direct learning model as a comparison, namely for class V students. The data results show Normal and Homogeneous with the resulting significance value > 0.05. Then the final test is the independent sample t-test to determine whether there is a difference in the average of the two unpaired samples from the data. Depending on the first decision by observing the column value Sig.t count (2-tailed) or P-value, required if the value of Sig. t-count 0.05, then H0 is accepted, and if the value of Sig. t-count 0.05, then H0 is rejected. From the second decision, H0 is rejected, and H0 is not enough to be accepted. The results showed that learning mathematics with the Flipped Classroom learning model for blind students in the covid-19 pandemic had a more positive effect than the results of learning mathematics in a direct learning class or without any treatment with the Flipped Classroom model.